Reference Intervals and Percentile Curves of Echocardiographic Left Ventricular Mass, Relative Wall Thickness and Ejection Fraction in Healthy Children and Adolescents - Diaz, Alberto Alejandro (2018)
Despite the clinical utility of echocardiography to measure cardiac target organ injury (TOI) there are scarcities of data about the reference intervals (RIs) and percentiles of left ventricular (LV) mass (LVM) and derived indexes (LVMI and LVMI2.7), relative wall thickness (LVRWT) and ejection fraction (LVEF) from population-based studies in children and adolescents. The aim of this study was to generate reference intervals RIs of LVM and derived indexes (LVMI and LVMI2.7), LVRWT, and LVEF obtained in healthy children, adolescents, and young adults from a South-American population. Echocardiographic studies were obtained in 1096 healthy subjects (5–24 years). Age and sex-specific RIs of LVM, LVMI, LVMI2.7, LVRWT, and LVEF were generated using parametric regression based on fractional polynomials. After covariate analysis (i.e., adjusting by age, body surface area) specific sex-specific RIs were evidenced as necessaries. Age and sex-specific 1st, 2.5th, 5th, 10th, 25th, 50th, 75th, 90th, 95th, 97.5th, and 99th percentile and curves were reported and compared with previously reported RIs. RIs showed high concordance and complementarity with what was previously reported for the population of North-American children (0–18 years old). In conclusion, in children and adolescents the interpretation of the LVM, LVMIs, LVRWT, and LVEF RIs requires sex-related RIs. This study provides the largest Argentinean database concerning RIs and percentile curves of LVM, LVMIs, LVRWT, and LVEF as markers of cardiac TOI obtained in healthy children and adolescents. These data are valuable in that they provide RIs values with which data of populations of children, adolescents can be compared.